Analisis daya tampung beban pencemaran Sungai Kampar Kiri Kabupaten Kampar Provinsi Riau - Muhammad Hidayatuddin; Usman M Tang; Rifardi Rifardi (Jurnal Zona, 2017)
The objectives of this study are to identify the pollutant sources location, analyze pollution load and pollution load carrying capacity of BOD (Biologycal Oxygen Demand), COD (Chemical Oxygen Demand) and TSS (Total Suspended Solid) concentrations; The QUAL2Kw methods application for modeling process of the main river were divided into nine reach, where Sibayang River (kilometre 86,629) as the headwater and Mentulik village as the downstream boundaries (km 0). The water samples where selected at ten points, with five of them are located at the main river and the rest of five at the tributaries. The modeling used water quality data on pollutant sources as input and the main river water quality data as a comparison.Based on the results of the study, total pollution load of BOD are 4,83 Tons/hour and total pollution load carrying capacity of BOD are 2,65 Tons/hour, it means a pollution load carrying capacity for BOD has been exceeded for 2,18 Tons/hour. The total pollution load of COD are 8,16 Tons/hour and total pollution load carrying capacity of COD are 8,45 Tons/hour, it means a pollution load carrying capacity for COD has not been exceeded and the main river still capable to recieve the pollution load of COD for 0,29 Tons/hour. Total pollution load of TSS are 55,90 Tons/hour and total pollution load carrying capacity of TSS are 12,45 Tons/hour, it means a pollution load carrying capacity for TSS has been exceeded for 43,45 Tons/hour. Generally total pollution load carrying capacity of BOD and TSS has been exceeded, and a total pollution load carrying capacity for COD has not been exceeded, nevertheless if review is based on river reach, an excessing of BOD pollution load has been occurred at km 18 - 1 for 1, 37 Tons/hour, COD pollution load for 2, 38 Tons/hour at km 45 - 40 and TSS pollution load for 32, 54 Tons/hour in the Teso River